Le imprese del generale Jean-Louis Rabutin de Bussy lungo il Danubio, 1697 - Nemeth, Gizella; Papo, Adriano (Études sur la Région Méditerranéenne, 2024)
Once the battle of Zenta (Senta, now in Serbia) was concluded (September 11th, 1697), where the Ottomans made up for a disastrous defeat from the imperial army of Eugene of Savoy, because of the impossibility of conquering Temesvár, also due to the now advanced autumn season, it was undertaken by the prince of Savoy a raid in the heart of Bosnia, which brought his army up to the rich merchant city of Sarajevo. Parallel to the Bosnian expedition, a diversion of the troops of cavalry general Jean-Louis Rabutin de Bussy took place against the Danube fortresses of Új-Palánka (Palanka) and Páncsova (Pančevo); the goal was to facilitate the raid in Bosnia, diverting the attention of the Ottomans from that front. The expedition began on 26 October 1697 starting from Déva, on the border between Transylvania and Banat; 3,000 horsemen, a body of the Rascian militia, six field artillery pieces and a mortar were part of it. The assault on Új-Palánka was scheduled for dawn on November 6th, 1697; momentarily suspended due to the arrival of some Turkish ships, from which a hundred men landed on the mainland as reinforcements for the garrison of the Turkish fort, it was resumed with continuous fire, vigorously opposed by the Turkish garrison. At this point the assault on the fort was carried out from another direction with the use of the reserve and took the besieged by surprise: the imperials opened a gap in the palisade with axes and entered the fort vehemently. Only a few Turks managed to save themselves, a lot of them was killed, or thrown into the Danube or taken prisoner. The news of the fall of Új-Palánka preceded the arrival of the imperials in Páncsova, which is why the Turkish garrison, frightened, burned everything and fled, leaving the artillery in place.